Teaching and learning : building effective pedagogies - Howell, Jennifer (2014)
Teaching and Learning: Building Effective Pedagogies introduces pre-service teachers to the principles of teaching across the early childhood, primary and middle years of school. The book guides students to gradually build theoretical knowledge and practical skills to prepare for their classroom experience. It covers the journey to becoming a teacher - the process and pedagogies needed to meet the diverse needs of students, comprehensive coverage of the phases of learning and development and explores the wider contexts of school culture, professional responsibilities and the transition from pre-service to practice.